Behavioral Barriers to Stop Female Genital Mutilation/Cutting in South Ethiopia: An Exploratory Qualitative Study of the Perspective of Women - Lejore Sibamo E; Bitew Workie S (Dove Medical Press, 2022)
Ephrem Lejore Sibamo,1 Shimelash Bitew Workie2 1School of Public Health, College of Medicine and Health Sciences, Hawassa University, Hawassa, Ethiopia; 2School of Public Health, College of Medicine and Health Sciences, Wolaita Sodo University, Wolaita Sodo, South EthiopiaCorrespondence: Ephrem Lejore Sibamo, Email ephreml@hu.edu.etBackground: Female genital mutilation or cutting (FGM/C) is an act that violates the rights of girls and women and causes serious medical complications. Approximately 200 million women have undergone circumcision in 31 countries. Ethiopia, in particular, has the largest number of women who undergone FGM/C. Unfortunately, there has been minimal research into the reasons for this high prevalence in the country. Hence, this study has been conducted to explore behavioral barriers to stopping FGM/C in Southern Ethiopia.Methods: An exploratory qualitative study was employed from October to November 2021 in two purposively selected zones of Southern Ethiopia. A purposive sampling technique was used to select respondents from the two zones. A total of fourteen study participants were selected and interviewed in-depth to obtain responses from various perspectives. A thematic content analysis was conducted to analyze the data collected from the field.Findings: The study revealed that FGM/C is widely practiced in the study area. Respondents were found to have poor awareness and positive attitude towards continuation of FGM/C. This is possibly due to the social and cultural acceptability of the practice and influences from peers, families, future marriage partners and the community. The study shows that women are more likely to be circumcised because they want to be respected by their community, to be considered eligible for marriage and to avoid stigma and discrimination.Conclusion: The continued practice of FGM/C was in considerable state to require the development of intervention strategies in order to eliminate it by 2030. The study's findings recommend stronger legal actions against those who perform FGM/C, alongside behavior change communication interventions, to improve awareness of its risks and encourage the community to stop FGM/C.Keywords: female genital mutilation, female genital cutting, behavioral barriers, Southern Ethiopia